Multiple sarcomatoid carcinoma of the small intestine with perforation as the initial symptom: case report and review of the literature - Fu, Jixin; Kong, Qingbin; Sui, Xin; Wang, Xinjian (Frontiers in Oncology, 2024)
BackgroundSarcomatoid carcinoma of the small bowel is an exceedingly rare gastrointestinal tumor characterized by a biphasic cellular pattern of epithelioid and mesenchymal-like cells. Due to its rarity and non-specific clinical presentation, it is frequently misdiagnosed, and there is a lack of standardized management guidelines. We report a case of multiple sarcomatoid carcinoma of the small intestine, presenting initially with gastrointestinal perforation. Additionally, we conducted a comprehensive review and analysis of the clinical manifestations, immunohistological characteristics, and prognostic factors associated with small intestinal sarcomatoid carcinoma, aiming to enhance diagnostic accuracy and therapeutic strategies for this rare malignancy.Case presentationAn 82-year-old man was admitted with a 1-week history of abdominal pain, exacerbated by the onset of fever in the last 24 hours. Abdominal CT revealed thickening of the small intestinal wall and free gas within the mesenteric space, indicating gastrointestinal perforation. Emergency surgery identified multiple tumors in the small intestine, accompanied by perforation. Postoperative pathology confirmed the diagnosis of sarcomatoid carcinoma of the small intestine.ConclusionWe report a rare case of sarcomatoid carcinoma of the small intestine and conduct a thorough literature review to offer new insights into its diagnosis, treatment, and prognosis. This highly malignant tumor, predominantly found in the jejunum and ileum, is characterized by high recurrence and metastasis rates, leading to a poor prognosis. Notably, postoperative radiotherapy does not improve outcomes. Abdominal CT is highly sensitive for detecting small bowel tumors but cannot confirm SCA due to its nonspecific imaging features. In contrast, small enteroscopy or capsule endoscopy offers greater diagnostic clarity. Increased awareness among clinicians is crucial for early detection and intervention.